Acetylcholine receptor antibody characteristics in myasthenia gravis. II. Patients with penicillamine-induced myasthenia or idiopathic myasthenia of recent onset. - Vincent, A (1982)
Anti-acetylcholine receptor (anti-AChR) antibody characteristics including light chain, IgG subclass, avidity for denervated human acetylcholine receptor and reaction with various human and mammalian AChR preparations were examined in 11 patients who developed myasthenia during penicillamine treatment of rheumatoid arthritis. Results were compared with those already reported in 35 patients with generalized idiopathic myasthenia gravis (MG). We found significant differences in the avidity and the light chain of the anti-AChR. However, anti-AChR characteristics in 12 patients with recent onset (less than 4 months' duration) idiopathic MG did not differ significantly from those in patients with penicillamine-induced MG. In the patients with generalized MG a trend was found towards higher percentage of kappa light chain and higher anti-AChR avidity with duration of disease. Anti-acetylcholine receptor antibodies in penicillamine-induced myasthenia gravis therefore appear to be similar to those of idiopathic myasthenia gravis of recent onset.